Digital Citizenship of People - Suphattanakul, Onuma; Maliwan, Ekarach (CENTRAL ASIA AND THE CAUCASUS, 2022)
Digital citizenship is the proper use of digital technologies by citizens. So being a good digital citizen needs certain talents and attributes. This study's goals were to (1) assess people's digital citizenship and (2) examine the effect of digital citizenship attributes on the digital citizenship. This research used an online survey as a quantitative technique. The study included 438 residents of HatYai and Songkhla Municipality in Thailand. The data were analyzed using mean, standard deviation, correlation coefficient, and regression to evaluate the relationships between variables and hypotheses. The findings showed high levels of digital citizenship in both municipalities, including (1) digital citizen identity, (2) digital activities, (3) skill and capacity for digital environment, and (4) digital ethics. The results also showed that people's digital citizenship was strongly linked to (1) digital access, (2) care and nurturing, (3) knowledge and understanding, (4) ethical reasoning, and (5) self-control. The findings may help improve digital citizenship. The findings may also help create future policies, regulations, and infrastructure to properly promote digital citizenship.